The Use of Religion Among HIV-Infected African American Women - Morse, Edward V. (Journal of religion and health, 2000)
A study of the associations among physical and mental health and differential patterns of religiosity among African American women was conducted with a sample of 253 participants: 104 HIV-infected, 46 chronically ill (not HIV-infected), and 103 healthy subjects. Participants' uses of private (i.e., prayer) and public (i.e., church attendance) forms of religiosity were assessed using data from semi-structured interviews. The relationship between religiosity and mental health exhibited an incongruous pattern, differing across health condition and forms of religious behavior. The practice of public religiosity was found to be inversely associated with engagement in high-risk health behaviors among HIV-infected and healthy women but not among the chronically ill. Although private religiosity was unrelated to participants' perceptions of physical health, public religiosity was positively associated with physical health among HIV-infected women and inversely associated with their CD4 count. Finally, having a sense of control over one's health was positively related to religiosity. Results from this study support the important role religion plays for persons faced with chronic terminal diseases, as in the case of HIV/AIDS.